2019
DOI: 10.1155/2019/4109150
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine-Induced Hyponatremia in an Elderly Male Patient with Treatment-Refractory Major Depressive Disorder

Abstract: Several classes of antidepressants can induce syndrome of inappropriate antidiuretic hormone hypersecretion (SIADH), thereby causing hyponatremia. Initial symptoms of hyponatremia include neuropsychiatric and gastrointestinal manifestations can mimic depression, especially in elderly people with multiple somatic complaints. Here we present a case of a 68-year-old man with treatment-refractory depression and general anxiety disorder who developed duloxetine-induced hyponatremia. His symptoms of hyponatremia inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The patient was diagnosed with SIADH and duloxetine cross-titrated to escitalopram. The patient's hyponatremia resolved approximately eight days after discontinuing duloxetine [15].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The patient was diagnosed with SIADH and duloxetine cross-titrated to escitalopram. The patient's hyponatremia resolved approximately eight days after discontinuing duloxetine [15].…”
Section: Discussionmentioning
confidence: 97%
“…There are multiple reports of patients developing hyponatremia upon initiation or while taking chronic duloxetine [7][8][9][10][11][12][13][14][15][16][17][18]. We present a case of acute severe hyponatremia due to an overdose of duloxetine, which has not been previously described.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is a critical consideration as many of the symptoms of hyponatremia, particularly generalized malaise and alterations in appetite can mimic symptoms of depression. A recent case report documented duloxetine induced hyponatremia, including symptoms such as "unsteady gait, dizziness, nausea, general malaise and poor appetite," resolved by discontinuing duloxetine [14]. Serotonin Norepinephrine Reuptake Inhibitors (SNRIs), such as duloxetine, have been associated with syndrome of inappropriate antidiuretic hormone (SIADH) with resulting hyponatremia.…”
Section: Antidepressants and Non-steroidal Anti-inflammatory Drugs (Nmentioning
confidence: 99%
“…Hyponatremia results from an inappropriately high release of antidiuretic hormone (ADH) from the posterior pituitary, which results in an excess retention of water and a low serum osmolality. In particular SNRIs act primarily to inhibit the reuptake of both serotonin and noradrenaline, and in experimental models it has been shown that both serotonin and noradrenaline can result in the increased release of ADH (in rat models serotonin (5-HT) activated 5-HT1A receptors cause sympathoexcitation of 5HT1C and 5HT2 receptors and the release of ADH; also stimulation of the paraventricular and supraoptic nuclei with norepinephrine can increase release of ADH within the serum) [14]. Therefore, through these mechanisms it is hypothesized that SNRIs cause SIADH in patients, a life-threatening side effect that must be monitored for by clinicians.…”
Section: Antidepressants and Non-steroidal Anti-inflammatory Drugs (Nmentioning
confidence: 99%